The Art of Goodbye: Planning Final Arrangements - Lynda Spence (EDIS)
The consumer is faced with complex personal decisions while making final arrangements. Final arrangements might include a religious ritual, service, tribute, funeral, and/or burial. This 7-page fact sheet, part of a new series entitled The Art of Goodbye: End of Life Education series, is designed to help in the development of a final arrangements plan using a coordinated approach. This document discusses the Funeral Rule, determinants, funeral providers, types of final arrangements, tissue or organ donation, body donation, preplanning, and prepaying. Written by Lynda Spence, and published by the UF Department of Family, Youth and Community Sciences, July 2016.